Pengaruh Penggunaan Bahan Bakar Biosolar, Biosolar Dengan Aditive Dan Pertamina Dex Pada Mitsubishi L-300 Terhadap Kepekatan Asap - Ponidi .; Ilham Miftakhur Rohman (Rekayasa Material, Manufaktur dan Energi, 2021)
Exhaust gas emissions from vehicles are felt to increase with the growth of vehicles on the road, especially the growth of commercial diesel-engined vehicles. The main objective of this study is to determine the quality of fuel that can affect the level of diesel engine smoke density. The test is carried out by taking the sampling test method on vehicles that are familiar to people used by the Mitsubishi L300 diesel small truck and smoke density testing using a Smoke Tester tool. The testing process uses different fuel variants, namely: Bio Solar, Bio Solar added with additives, Pertamina Dex. It is expected that with several different fuel variables, it can determine how much influence the quality of the fuel has on the smoke density caused by the Diesel engine. The testing process at an engine speed of 1500 rpm, 2500 rpm to 4200 rpm for each variable of the testing process at each engine speed is carried out by the test process three times, and then the average results are taken from the entire testing process to get the most accurate results. Bio Solar fuel obtained the highest smoke density results at maximum engine speed, namely 4200 rpm with the highest average smoke density value of 40.1%, Bio Solar fuel plus addictive substances obtained the highest smoke density results at a maximum engine speed of 4200 rpm with an average value The highest smoke density was 31.23% while using Pertamina Dex fuel, the highest smoke density results were obtained at maximum engine speed, namely 4200 rpm with the highest average smoke density value of 18.4%.